Hunter's Horn - Arnow, Harriette Louisa Simpson, 1908-1986 (Book collections on Project MUSE., 1997)
Michigan State University Press is proud to announce the re-release of Harriette Simpson Arnow''s 1949 novel Hunter''s Horn, a work that Joyce Carol Oates called ""our most unpretentious American masterpiece."" In Hunter''s Horn, Arnow has written the quintessential account of Kentucky hill people-the quintessential novel of Southern Appalachian farmers, foxhunters, foxhounds, women, and children. New York Times reviewer Hirschel Brickell declared that Arnow ""writes...as effortlessly as a bird sings, and the warmth, beauty, the sadness and the ache of life itself are not even once.